Diverse maturity-dependent and complementary anti-apoptotic brakes safeguard human iPSC-derived neurons from cell death - Wilkens, Ruven; Hoffrichter, Anne; Kleinsimlinghaus, Karolina; Bohl, Bettina; Haag, Carolin; Lehmann, Nadja; Schmidt, Malin; Muñoz Perez-Vico, Elena; Wangemann, Julia; Rehder, Klara Franziska; Horschitz, Sandra; Koehr, Georg; et al. (Cell death & disease, 2022)
In humans, most neurons are born during embryonic development and have to persist throughout the entire lifespan of an individual. Thus, human neurons have to develop elaborate survival strategies to protect against accidental cell death. We set out to decipher the developmental adaptations resulting in neuronal resilience. We demonstrate that, during the time course of maturation, human neurons install a complex and complementary anti-apoptotic signaling network. This includes i.) a downregulation of central proteins of the intrinsic apoptosis pathway including several caspases, ii.) a shift in the ratio of pro- and anti-apoptotic BCL-2 family proteins, and iii.) an elaborate regulatory network resulting in upregulation of the inhibitor of apoptosis protein (IAP) XIAP. Together, these adaptations strongly increase the threshold for apoptosis initiation when confronted with a wide range of cellular stressors. Our results highlight how human neurons are endowed with complex and redundant preemptive strategies to protect against stress and cell death.